Evaluation of the impact of convolution masks on algorithm to supervise scenery changes at space vehicle integration pads - Francisco Carlos P. Bizarria; Silvana Aparecida Barbosa; José Walter P. Bizarria; João Maurício Rosário (Journal of Aerospace Technology and Management, 2011)
The Satellite Launch Vehicle developed in Brazil employs a specialized unit at the launch center known as the Movable Integration Tower. On that tower, fixed and movable work floors are installed for use by specialists, at predefined periods of time, to carry out tests mainly related to the pre-launch phase of that vehicle. Outside of those periods it is necessary to detect unexpected movements of platforms and unauthorized people on the site. Within that context, this work presents an evaluation of different resolutions of convolution mask and tolerances in the efficiency of a proposed algorithm to supervise scenery changes on these work floors. The results obtained from this evaluation are satisfactory and show that the proposed algorithm is suitable for the purpose for which it is intended.